Analisis Sumber-Sumber Pendapatan Daerah dan Pengaruhnya Terhadap Produk Domestik Regional Bruto Provinsi Nusa Tenggara Timur Tahun 2015-2019 - Muhammad Fadlin Baharsyah (Program Studi Ekonomi Pembangunan, 2022)
Gross Regional Domestic Product (PDRB) is the amount of added value generated for all business and service areas in a region, applying the total value of final goods and services produced by all economic units. Gross Regional Domestic Product (PDRB) is influenced by the realization of income which is a fiscal policy adopted by regional governments. The purpose of this study was to determine the average source of regional income, analyze the influence of PAD, DAU and DAK on PDRB of Regency / City Government in East Nusa Tenggara. Based on the results of research regarding the Analysis of Regional Income Sources and Its Effect on the Gross Regional Domestic Product of the Province of NTT in 2015-2019, conclusions can be drawn, namely: PAD has a negative and insignificant effect on GRDP in districts/cities in NTT Province in 2015-2019, DAU has a positive and significant effect on GRDP in districts/cities in NTT Province in 2015-2019, DAK has a positive and significant effect on GRDP in districts/cities in NTT Province in 2015-2019